2007
DOI: 10.1111/j.1571-9979.2007.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight Mediation: A Learning‐Centered Mediation Model

Abstract: Insight mediation is the name we have given to the model of mediation that is taught and practiced at Carleton University in Ottawa, Canada. The name has evolved from our efforts to situate the model in relation to the transformative and narrative styles of mediation. Drawing upon the work of Canadian philosopher Bernard Lonergan and his theory of insight, mediators practicing this model seek direct and inverse insights into what the conflict means to each party by discovering what each party cares about and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…On the other hand, mediators who purposely and systematically reflect on practice could use other terms for what they do, such as reflection, self‐reflection, self‐assessment, self‐understanding, or consciousness (Bronson, ; Friedman, ; McGuigan & Popp, , ; McGuire & Inlow, ; Seibt, ). Picard and Melchin () developed the “Insight” mediation model, which can arguably be described as a reflective practice model of mediation in which mediators encourage both themselves and parties to verify what they are observing and how they are interpreting it through a series of testing questions. More research is needed to identify mediators and trainers who may be carrying out modes of reflective practice under different titles.…”
Section: Reflective Practicementioning
confidence: 99%
“…On the other hand, mediators who purposely and systematically reflect on practice could use other terms for what they do, such as reflection, self‐reflection, self‐assessment, self‐understanding, or consciousness (Bronson, ; Friedman, ; McGuigan & Popp, , ; McGuire & Inlow, ; Seibt, ). Picard and Melchin () developed the “Insight” mediation model, which can arguably be described as a reflective practice model of mediation in which mediators encourage both themselves and parties to verify what they are observing and how they are interpreting it through a series of testing questions. More research is needed to identify mediators and trainers who may be carrying out modes of reflective practice under different titles.…”
Section: Reflective Practicementioning
confidence: 99%
“…The Insight approach was fi rst developed by Melchin ( 2007 , Melchin andPicard 2008 ), in an attempt to generate a clearer understanding of the process that sometimes takes place in a negotiation or mediation context, when one or more parties experience a shift in perspective that enables them to orient towards the other in different ways, thus opening up the space for more collaborative efforts at resolving the confl ict. Melchin and Picard observed that confl ict was often most diffi cult to resolve when either side believed that what deeply mattered to them-their cares-was threatened by what mattered to the other party.…”
Section: Decision-makers As Historically Situated Purposive Actorsmentioning
confidence: 99%
“…The Insight approach to confl ict (Picard and Melchin 2007 ;Melchin and Picard 2008 ;Sargent et al 2011 ;Picard and Jull 2012 ;Price 2013 ) views confl ict resolution as a communicative learning process through which parties gain greater understanding or insight into the cares and threats that motivate both the self and the other and which in turn fuel the confl ict or create obstacles to a collaborative decisionmaking or negotiation process. Central to the Insight approach is an awareness of how the parties' perceptions are infl uenced by the interpretive framework the parties develop for making sense of the confl ict or negotiation interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Effective mediators are flexible and display competence “in unique, uncertain and conflicted situations of practice” (Schön 1987: 22). Mediation practice can be described as a form of professional artistry involving a wide range of tacit knowledge, skills, a certain amount of intuition, insight, and even improvisation (Schön 1987; Lang and Taylor 2000; Picard and Melchin 2007). There is rarely a clearly “right” move to make at any given stage of the process but rather a number of alternatives “where the notion of being ‘correct’ gives way to broader assessments of value, such as aesthetic appeal, originality, usefulness, self‐expression, creativity and so on” (Biggs 1999: 154).…”
Section: Teaching Mediationmentioning
confidence: 99%